Bentuk Sapaan Kekerabatan Bahasa Sula dalam Perspektif Gender - Nurhayati Fokkaya (Kantor Bahasa Provinsi Maluku Utara, 2016)
In gender perspective of Sula language, there is a different form of addressing male and female in nucleus family. This can be seen in the use of second single pronoun mon “you” and gu “you”. This kind of addressing covers the usual dimension or (unequal) and is used by anyone. More dominantly, women use polite addressing (equivalent) when greeting men, as in the word kim “you” referred to singular pronoun and gi “you” referred to plural pronoun. in Sula kinship, the word